2014
DOI: 10.1210/jc.2014-1572
|View full text |Cite
|
Sign up to set email alerts
|

Recovery From SIADH-Associated Osteoporosis: A Case Report

Abstract: This case provides evidence for a causal relationship between SIADH and chronic hyponatremia and impaired bone metabolism that can lead to severe secondary osteoporosis. The effect on bone metabolism is at least partially reversible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…However, when the analysis is expanded beyond the analysis of a single serum Na ϩ value (as is done in the Rotterdam study) to include the variable of chronic hyponatremia over at least 1 year, osteoporosis odds increase to almost 4-fold. That chronic hyponatremia is strongly associated with increased odds of osteoporosis whereas prior hyponatremia is associated with an increased odds of osteoporosis to a lesser extent is consistent with the proposed pathogenesis of hyponatremia-induced osteoporosis in animal studies and recent case reports (8,14). A study of single serum Na ϩ values 14 days before or after imaging suggested a modest dose-response between increasing serum Na ϩ and increasing total hip bone mineral content, BMD, and T-score (20).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…However, when the analysis is expanded beyond the analysis of a single serum Na ϩ value (as is done in the Rotterdam study) to include the variable of chronic hyponatremia over at least 1 year, osteoporosis odds increase to almost 4-fold. That chronic hyponatremia is strongly associated with increased odds of osteoporosis whereas prior hyponatremia is associated with an increased odds of osteoporosis to a lesser extent is consistent with the proposed pathogenesis of hyponatremia-induced osteoporosis in animal studies and recent case reports (8,14). A study of single serum Na ϩ values 14 days before or after imaging suggested a modest dose-response between increasing serum Na ϩ and increasing total hip bone mineral content, BMD, and T-score (20).…”
Section: Discussionsupporting
confidence: 60%
“…Animal model studies suggest that chronic hyponatremia can cause or accelerate osteoporosis, organ dysfunction, and senescence (8,9). Also, at least two case-control studies and two cohort studies suggest an association between osteoporosis or fracture and hyponatremia (10 -13), and a recent case report describes a patient with partial reversal of severe osteoporosis after correction of chronic hyponatremia (14). Furthermore, clinical studies indicate that acute hyponatremia can induce a broad spectrum of neurological manifestations, ranging from mild nonspecific symptoms to more significant disorders.…”
mentioning
confidence: 99%
“…This indicated a mechanism of hyponatremia-induced osteoporosis. Surgical recovery from SIADH resulted in significant spontaneous improvement in BMD in the lumbar vertebrae [16]. Further in vivo research is warranted to establish whether inducing or developing dilutional hyponatremia, i.e., through increased water intake or by administering analogs of vasopressin, increases bone resorption similarly to in vitro studies in rat models.…”
Section: Hyponatremia As a Stimulus Of Bone Resorptionmentioning
confidence: 99%
“…In this patient, lumbar BMD spontaneously improved after the surgical excision of an antidiuretic hormone (ADH)-secreting esthesioneuroblastoma, which was followed by serum [Na ? ] normalization [14]. At variance with these findings, data analysis from the Rotterdam study indicated that the observed association of mild hyponatremia with an increased risk of vertebral and non-vertebral fractures was independent of BMD and more likely due to an effect on bone quality [6].…”
Section: Introductionmentioning
confidence: 98%